The Existence of Customary Law in the Protection of Customary Land Rights of Indigenous Peoples in Indonesia - Loso Judijanto; Angga Aldilla Gussman (PT. Anagata Sembagi Education, 2026)
Customary law is a legal system that lives and develops in Indonesian society and has an important role in the regulation and protection of customary land rights of indigenous peoples. The recognition of the existence of customary law communities and their traditional rights has been constitutionally affirmed through Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. However, this recognition has not been fully implemented effectively in the national legal system, especially in the field of land. This study aims to analyze the existence of customary law in the protection of customary land rights of indigenous peoples and assess the consistency of its regulation in laws and regulations, especially Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles. The research method used is normative juridical with a legislative approach and a conceptual approach. The results of the study show that the recognition of customary rights in the UUPA is still conditional and tends to be subordinate to the concept of the right to control by the state. This condition creates legal uncertainty and weakens the protection of indigenous peoples' rights over their territory. In addition, the lack of harmonization of various sectoral regulations further increases the potential for agrarian conflicts. Therefore, it is necessary to strengthen regulations and harmonize laws that place customary law as an integral part of the national legal system in order to realize the protection of customary land rights that are just.